2017
DOI: 10.1136/bmj.j510
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of reduced dose non-vitamin K antagonist oral anticoagulants and warfarin in patients with atrial fibrillation: propensity weighted nationwide cohort study

Abstract: Objective To examine clinical effectiveness and safety of apixaban 2.5 mg, dabigatran 110 mg, and rivaroxaban 15 mg compared with warfarin among patients with atrial fibrillation who had not previously taken an oral anticoagulant. Design Propensity weighted (inverse probability of treatment weighted) nationwide cohort study. Setting Individual linked data from three nationwide registries in Denmark. Participants Patients with non-valvular atrial fibrillation filling a first prescription for an oral anticoagula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
275
6
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(315 citation statements)
references
References 43 publications
17
275
6
10
Order By: Relevance
“…In the largest study of NOAC dosing and outcomes, a nationwide Danish analysis suggested differential outcomes among different reduced‐dose NOACs compared with warfarin, but none of the comparisons was statistically significant 18. Furthermore, it is not clear from that analysis what proportion of patients in each drug group qualified for the reduced dose based on regulatory recommendations—our US data suggest that more than half of these patients may be inappropriately underdosed, and this could certainly account for a difference in clinical outcomes across very large populations.…”
Section: Discussionmentioning
confidence: 99%
“…In the largest study of NOAC dosing and outcomes, a nationwide Danish analysis suggested differential outcomes among different reduced‐dose NOACs compared with warfarin, but none of the comparisons was statistically significant 18. Furthermore, it is not clear from that analysis what proportion of patients in each drug group qualified for the reduced dose based on regulatory recommendations—our US data suggest that more than half of these patients may be inappropriately underdosed, and this could certainly account for a difference in clinical outcomes across very large populations.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence from observational studies that dose-adjusted DOAC therapy is often inappropriately prescribed, being underdosing more frequent than overdosing [100,101], and that this behavior might be associated with lower efficacy and safety outcomes [102].…”
Section: Evidence From Real-world Studiesmentioning
confidence: 99%
“…from those included in the strictly defined study populations in the pivotal RCTs that are carefully followed up at regular protocol-based intervals. In addition, clinicians may sometimes choose NOAC dosing regimens that were not well studied in the RCTs 4 . Notwithstanding their limitations, well conducted post-approval large observational studies are of key importance to provide data (so called "real-world" data, RWD) on the effectiveness and safety of NOACs used outside the RCTs, in a routine clinical setting 5 .…”
Section: Editorialmentioning
confidence: 99%